Pre-elementary Children With Imperfect Letter-Name Knowledge Are at Great Risk of Reading Difficulty in First Grade: One-Year Longitudinal Study in Japanese Hiragana - Okumura, Yasuko; Kita, Yosuke; Kitamura, Yuzuki; Oyama, Hoko (Frontiers in Education, 2022)
While letter-naming ability is a well-known preschool predictor of the later acquisition of literacy, little is known about an appropriate benchmark (i.e., how many letter names children must know at a given age) and how it may vary among different writing systems. The present study aimed to establish a letter-naming benchmark in Japanese Hiragana for pre-elementary children (age five to six years) and examined whether this benchmark predicts risk or success in later reading development via a one-year longitudinal survey. Children (N = 291) were assessed once in their pre-elementary year for Hiragana-naming accuracy and once in their first-grade year for oral reading fluency. As a result, the ability to name 40 of 45 letters was determined to be an optimal cut-off, and failure to meet it strongly predicted a risk of deficient reading fluency in first grade. These findings support the notion that Japanese children without near-perfect mastery of Hiragana-naming in their pre-elementary year are at great risk of reading difficulty in first grade. In addition, possible contrasts between Hiragana- and alphabet-naming indicated a need for further research in different languages and scripts to establish appropriate goals and policies for this foundational skill of reading in early education.